Pediatric and adolescent injury in skateboarding - Feletti, F.; Brymer, E. (Research in Sports Medicine, 2018)
Skateboarding has become an international action sport attractive to young people. For this reason, skateboarding has been promoted by some researchers as important for encouraging young people to become more physically active. However, skateboarding is also considered to be inherently dangerous by the medical and broader community and as a result skateboarding is banned in many places. This paper reviews scientific literature on the features, outcomes and risk factors related to skateboarding injuries. Findings suggest that while skateboarding injuries can be severe, skateboarding is not as dangerous as it might appear if appropriate risk management steps are taken. Skateboarding should be encouraged as a worthy physical activity and local communities should consider providing specialised, supervised spaces for young people to practice this sport.